No place - Strasser, Todd (Simon & Schuster BFYR, 2015)
Dan, a popular basketball star with a beautiful girlfriend, experiences a major upheaval when his family loses their home and is forced to move into the local tent city where the homeless live. Dan copes with his new situation by joining with other homeless residents to fight for better conditions, but his problems get even bigger when he learns that someone will stop at nothing to destroy the tent city.